Flocculation of dimorphic yeast benjaminiella poitrasii is altered by modulation of NAD-glutamate dehydrogenase - Joshi, C. V.; Ghormade, Vandana; Kunde, P.; Kulkarni, P.; Mamgain, H.; Bhat, Suresh K.; Paknikar, K. M.; Deshpande, Mukund V. (Bioresource Technology, 2010)
A strategy to control flocculation is investigated using dimorphic yeast, Benjaminiella poitrasii as a model. Parent form of this yeast (Y) exhibited faster flocculation (11.1 min) than the monomorphic yeast form mutant Y-5 (12.6 min). Atomic force microscopy revealed higher surface roughness of Y (439.34 rms) than Y-5 (52 rms). Also, the former had a zeta potential of -65.97 +/- 3.45 as against -50.21 +/- 2.49 for the latter. Flocculation of both Y and Y-5 could be altered by supplementing either substrates or inhibitor of NAD-glutamate dehydrogenase (NAD-GDH) in the growth media. The rate of flocculation was promoted by alpha-ketoglutarate or isophthalic acid and decelerated by glutamate with a statistically significant inverse correlation to corresponding NAD-GDH levels. These interesting findings open up new possibilities of using NAD-GDH modulating agents to control flocculation in fermentations for easier downstream processing. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Benjaminiella poitrasii; dimorphism; flocculation; NAD-glutamate dehydrogenase

Fungal cell membrane-promising drug target for antifungal therapy - Sant, D. G.; Tupe, Santosh Genba; Ramana, Chepuri V.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2016)
Increase in invasive fungal infections over the past few years especially in immunocompromised patients prompted the search for new antifungal agents with improved efficacy. Current antifungal armoury includes very few effective drugs like Amphotericin B; new generation azoles, including voriconazole and posaconazole; echinocandins like caspofungin and micafungin to name a few. Azole class of antifungals which target the fungal cell membrane are the first choice of treatment for many years because of their effectiveness. As the fungal cell membrane is predominantly made up of sterols, glycerophospholipids and sphingolipids, the role of lipids in pathogenesis and target identification for improved therapeutics were largely pursued by researchers during the last few years. Present review focuses on cell membrane as an antifungal target with emphasis on membrane biogenesis, structure and function of cell membrane, cell membrane inhibitors, screening assays, recent advances and future prospects.

Facile and solvent-free domino synthesis of new quinolidinyl-2,4-thiazolidinones: antifungal activityand molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Jha, Prakash C.; Shingate, Bapurao B. (Mini-Reviews in Medicinal Chemistry, 2018)
Objective: We have synthesized new quinolidinyl-thiazolidinones via Knoevenagel condensation-alkylation reaction, catalyzed by [Et3NH][HSO4]. The present approach offers several advantages such as higher yields, eco-friendly reaction condition and economic availability of the catalyst. Method: The newly synthesized compounds were evaluated for their in vitro antifungal activity against six fungal strains. Some of the synthesized conjugates displayed good to moderate antifungal activity. Conclusion: Again, the molecular docking study performed against the fungal sterol 14 alpha-demethylase (CYP51) showed an excellent binding affinity towards the enzyme which could rationalize the promising antifungal activity portrayed by these derivatives and provides a platform for structure based drug design.